2006
DOI: 10.1196/annals.1385.018
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Female Genital Mutilation

Abstract: Female genital mutilation (FGM) is a form of violence against women that has recently been labeled a public health issue. This article will define and describe the procedure as well as discuss its physical and psychological implications. An exploration of the cultural significance of the practice will shed light on its continued existence in underdeveloped and developed nations. In addition, an examination of suggested guidelines for creating and implementing effective interventions will ensue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Female genital cutting (FGC), also known as female circumcision and female genital mutilation, is a traditional practice common to most societies in north-eastern Africa, where it was almost universally conducted until some decades ago (Baron and Denmark, 2006;Klouman et al, 2005;Missailidis and Gebre-Medhin, 2000;Msuya et al, 2002;Tag Eldin et al, 2008;UNICEF, 2005). The World Health Organization (WHO) estimated that more than 130 million women are affected by FGC worldwide (WHO, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Female genital cutting (FGC), also known as female circumcision and female genital mutilation, is a traditional practice common to most societies in north-eastern Africa, where it was almost universally conducted until some decades ago (Baron and Denmark, 2006;Klouman et al, 2005;Missailidis and Gebre-Medhin, 2000;Msuya et al, 2002;Tag Eldin et al, 2008;UNICEF, 2005). The World Health Organization (WHO) estimated that more than 130 million women are affected by FGC worldwide (WHO, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As a result she will not get married [ 21 ] and will not be allowed to speak at gatherings. Worse still her families may suffer discrimination from the community for failing to follow the custom [ 22 ]. Thus, a woman cannot protect her daughter from the procedure even if she wants to [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…FGM may have various consequences, some immediate and some arising later in life. These consequences can be related to physical, psychological, reproductive, and sexual health [19][20][21]. A questionnaire-based cross-sectional study conducted in Saudi Arabia reported that over two-thirds of the study participants were aware of the health-related complications of FGM [4].…”
Section: Effects and Complications Of Female Genital Mutilationmentioning
confidence: 99%
“…A questionnaire-based cross-sectional study conducted in Saudi Arabia reported that over two-thirds of the study participants were aware of the health-related complications of FGM [4]. The occurrence and severity of the adverse events due to FGM are dependent upon many factors, including the hygiene of the environment, the skills of the person performing the procedure, the resistance of the child, and how susceptible the victim is to infections [21]. FGM has been previously nicknamed "three feminine sorrows" [22].…”
Section: Effects and Complications Of Female Genital Mutilationmentioning
confidence: 99%
See 1 more Smart Citation